ASUHAN KEPERAWATAN GERONTIK PADA LANSIA POST-STROKE DENGAN MASALAH RISIKO JATUH: STUDI KASUS - Rondonuwu, Junytha R; Momongan, Lieke; Gahunting, Niken (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2024)
Introduction: Post-stroke is a phase experienced by patients after passing the critical phase of a stroke. Dangerous conditions that need to be monitored include the risk of falling because it can cause more dangerous impacts, namely a decline in function and physiological conditions that occur in the elderly phase. Nurses play an important role in providing nursing care to the elderly with post-stroke. Objective: This study aims to describe the application of gerontic nursing care for post-stroke patients at the